Community-based curriculum in psychiatric nursing science - S Arunachallam; AC Botes; A Gmeiner (AOSIS, 2000)
As community-based health care delivery is now a prominent feature of the health care system in South Africa, nursing curricula are being challenged to prepare student nurses for community based nursing roles and responsibilities. The purpose of this study was to describe guidelines for a community-based curriculum in psychiatric nursing science for a nursing college in KwaZulu-Natal. A qualitative, quantitative, exploratory, descriptive and contextual design was employed. To reach the purpose of the study, a situational analysis was done in three phases to identify the principles for a community-based curriculum for psychiatric nursing science. Phase I: A document analysis of relevant government policies and legislation. Phase II: Statistics from psychiatric hospitals and community psychiatric clinics. Phase III: Focus group interviews with nurse educators and literature control and conceptual framework The principles obtained from the three phases were used to formulate the guidelines for a community-based curriculum in psychiatric nursing science (Phase IV). Eight guidelines with practical implications are described for the implementation of a Community-based curriculum in Psychiatric Nursing Science.